Proposta de implementação de um sistema de gestão escolar para as escolas de ensino técnico do estado do Pará - MONTEIRO, José Ramon da Conceição (2019)
This paper aims to report the development process of the Vulpiny School Management System for Juscelino Kubitschek de Oliveira State School of Agroindustrial High School in Marituba-PA, which is part of the network of Technical Education Schools of the State of Pará. The Vulpiny School Management System is a Web System that can be deployed in local infrastructure or in the cloud, such as Amazon or Google Cloud. It was designed for the computerization of the administrative routines of this school, among them: student enrollment, follow-up of internships and management of teachers and other employees with relevant functions to use it. The system was developed using Spring Boot, a framework for Java Web applications based on the MVC (Model-View-Controller) Architecture, HTML5, CSS3 and JavaScript and the database chosen was is MySQL. Was also adopted the modeling UML, looking for to produce diagrams that facilitate the understanding of the required functionalities, as well as the role that each actor would play in its use. Was also sought to offer screens with excellent distribution of components, buttons, menus and explanatory texts, to make the user experience as satisfying as possible.